THE SEVERITY OF STRESS IN FUNCTIONAL DYSPEPSIA COMPARED TO ORGANIC DYSPEPSIA - Tambunan, Asri Ludin; Lubis, Hanida; Siregar, Gontar A (Medicina Biomedica Journal, 2022)
Introduction: Dyspepsia is a collection of symptoms in the form of pain or discomfort centered in the upper abdomen. Discomfort specifically includes an immediate sense of fullness, burning, bloating in the upper abdomen, and nausea. Symptoms that arise due to various factors such as lifestyle smoking, alcohol, excess weight, stress, anxiety, and stress are relevant to dyspepsia. Objectives: To determine the severity of stress in patients with functional dyspepsia compared to organic dyspepsia at H. Adam Malik Medan Hospital.Methods: It is observational analytical research and is conducted witha cross-sectional design. The study sample was selected randomly,samplingpatients who met the criteria until the required number of samples were met, and 52 people obtained the sample. The data is analyzed withthe Exact Fisher test.Results: There is a relationship between patients who experience stress with the occurrence of Functional Dyspepsia. In normal people, organic dyspepsia is higher than functional dyspepsia.